Anti-Dermatophytes Activity of Macroalgal Extracts (Chara vulgaris) Isolated from Baghdad City-Iraq - Ahmed S. Dwaish (Journal of Global Pharma Technology, 2018)
In the present study, the metabolic andethanolic extracts of specie (Division: Chlorophyta)  Chara vulgaris was tested  for antifungal (Dermatophytes) activity for in vitro at concentration (100,50 and 25 mg/ml) against two clinical isolates of Dermatophytes fungi (Trichophyton rubrum and Trichophyton mentagrophytes) by measuring  percentage of inhibition growth. The results indicated that the hot ethanol extract of Chara vulgaris was more efficient(89.8 %) inhibition growth at concentration 100 mg/ml and the lowest effect was (20.4%) at concentration 25 mg/ml  against the tested pathogenic fungi.  Chemical analyses showed that the active chemical compounds for hot ethanolic and methanolic alga (Chara vulgaris )extracts  were contains alkaloids, phenols ,Terpenes , Steroids, Flavones, Resins ,Saponines and tannins. Finally the result of GC mass analysis for Chara vulgaris extracts proved the presence of many antimicrobial activity compounds.Keyword: Fresh water algae, Anti-Dermatophytes activity, Hot ethanolic and methanolic extracts, Baghdad City-Iraq.